Recuperação de neodímio a partir de fontes secundárias utilizando ácidos orgânicos e CO2 supercrítico - Reisdörfer, Gustavo (2019)
Technological innovation has brought with it a number of electro-electronic equipment, but its disposal has been faster, making these wastes a concern, as to their destination and the supply of raw materials. These equipments contain several materials with potential added value that can be recycled and reused. This is the case of neodymium (Nd), present in Hard Disk Drivers (HDDs), which is a rare earth, and makes up the list of critical and risky raw materials. The objective of this work was to study the recovery of Nd from permanent neodymium ironboron (NdFeB) magnets obtained from discarded HDDs using leaching organic acids. Leaches were performed under atmospheric pressure conditions and with the use of supercritical CO2 extraction. In addition, the behavior of NdFeB powders, roasted and unroasted (heat treatment) was evaluated to verify the potential of neodymium selectivity in relation to iron. In the initial stage, the HDDs were manually disassembled and the magnets removed from it. The magnet demagnetization tests were performed at high temperatures (300, 350 and 400 °C) varying the time (15, 30, 45 and 60 min). After this step, the magnets were comminuted in a ball mill to obtain particles smaller than 400 µm. Roasting (heat treatment) was performed at a temperature of 900 °C for 480 min. Atmospheric leaches were conducted to assess the influence of temperature (30, 50, 70 and 90 °C), acid concentration (0.2 to 1.2 M), solid: liquid ratio (1:10, 1:20, 1:30 and 1:50) and the best leaching time (10, 20, 30, 60, 120, 180, 360, 720 and 900 min). Extraction with supercritical CO2 was performed using different pressures (80, 100, 120 and 150 bar), temperatures (60, 70, 80 and 90 °C) and extraction times (5 to 120 minutes). The results showed that the best conditions found for atmospheric leaching for both malic acid and citric acid were 90 °C, 1.0 M and 1:20. Regarding the reaction time, for the roasting NdFeB powder 100% Nd recovery was achieved with 360 min of malic acid leaching. Citric acid leaching showed good efficiency up to 30 minutes of experiment, reaching 72.8% Nd recovery. In the supercritical CO2 extraction for the unroasted NdFeB powder at 90 °C and 120 bar, Nd recovery of 99.4% and 50.5% after 30 min was observed using malic acid and citric acid, respectively. For roasted NdFeB powder the efficiencies were 99.5% and 30.6% after 120 min using malic and citric acid at 90 °C and 100 bar respectively. Thus, the use of supercritical CO2 is highly effective for recovering Nd from the unroasted powder with malic acid, allowing a significant reduction in extraction time compared to atmospheric leaching from 360 to 30 min.